Development of PT SIER Accounting Information Systems: The Importance of User Participation and Satisfaction - Dirani, Aminah; Saputro, Achsan Adi; Handoyo, Vita Sitaresmi (Indonesian Journal of Sustainability Policy and Technology, 2024)
Rapid changes and developments affect information systems (including accounting information systems). These changes and developments are visible in managerial needs, perceptions, business environment, and accounting information technology. This requires an effective internal and external information system so management can detect effectively when conditions change and require a strategic response. Using accounting information systems is expected to greatly benefit the highly competitive business world. The determining factor for the success of information system development is important. Because some users at PT. SIER (Persero) is not satisfied with the information produced because the information created does not follow the decision-making needs, so the presentation of the resulting report is less accurate and not timely. Therefore, this research examines the influence of top management support, user participation, and user communication on user satisfaction in developing an accounting information system. Data were analyzed with a population of 53 managers and assistant managers at PT. SIER (Persero) used a census sampling technique or saturated sampling of 53 managers and assistant managers, and the data analysis technique used in this research was the multiple linear regression statistical test. The conclusion that can be drawn from the multiple linear regression statistical test is that top management support, user participation, and user communication positively affect user satisfaction in accounting information system developers at PT. SIER (Persero), so that the research hypothesis is proven true.